أثر برنامج مقترح لتدريس الكيمياء باستخدام أنشطة الذكاءات المتعددة على التحصيل ومهارات التفكير العليا وأنماط التعلم والتفكير لدى طلاب الصف الأول الثانوي - حسين، أشرف عبدالمنعم محمد (جامعة الأزهر - كلية التربية, 2019)
أثر برنامج مقترح لتدريس الكيمياء باستخدام أنشطة الذكاءات المتعددة على التحصيل ومهارات التفكير العليا وأنماط التعلم والتفكير لدى طلاب الصف الأول الثانوي. هدف البحث إلى معالجة انخفاض التحصيل ومهارات التفكير العليا لدى طلاب الصف الأول الثانوي وتعرف أثر برنامج تدريسي مقترح في الكيمياء باستخدام أنشطة الذكاءات المتعددة على أنماط التعلم والتفكير لديهم، ولتحقيق هذا الهدف تم استخدم المنهج شبه التجريبي الذي يأخذ بتصميم القياس القبلي والبعدي لمجموعتين، وأعداد برنامج مقترح لتدريس الكيمياء باستخدام أنشطة الذكاءات المتعددة، واختبارا للتحصيل، وآخر لمهارات التفكير العليا في الكيمياء، واختبارا لأنماط التعلم والتفكير، تم تطبيق أداتي البحث قبليا على مجموعتي البحث، حيث تكونت عينة البحث من (58 طالباً) من طلاب الصف الأول الثانوي ذوى نمط جانب الدماغ الأيسر، (29 طالباً) للمجموعة التجريبية، و(29 طالباً) للمجموعة الضابطة، ثم درسوا وحدة "المادة - الخواص والتغيرات" باستخدام البرنامج المقترح، ثم تم تطبيق كلٍ من الاختبارين بعدياً على مجموعة البحث، وذلك خلال الفصل الثاني للعام الدراسي (1438- 1439)ه. وأسفرت نتائج البحث عن وجود فروق دالة إحصائياً عند مستوى (0.05) بين متوسطات درجات طلاب الصف الأول الثانوي ذوي نمط جانب الدماغ الأيسر في التطبيق القبلي والبعدي في اختبار التحصيل ومهارات التفكير العليا لصالح التطبيق البعدي، كما أسفرت النتائج عن وجود أثرٍ للبرنامج المقترح على التحصيل وتنمية مهارات التفكير العليا ونمط جانب الدماغ الأيمن والمتكامل لدى الطلاب ذوي نمط جانب الدماغ الأيسر بالصف الأول الثانوي، وفي ضوء هذه النتائج قدَّم الباحث بعض التوصيات والمقترحات.
A Suggested Program to Teaching Chemistry by Using a Multiple Intelligences Activities and Its Impact on the Higher Thinking Skills and Style of Learning and Thinking of the First grade secondary Students. This research aimed to treating the lowest achievement and highe r thinking skills of the students in the first grade of secondary, and identifying the impact of a suggested program to teaching Chemistry by Using the a multiple intelligences activities on and Style of Learning and Thinking, To achieve that, Its' using the semi-experimental approach which includes designing pre and post measurement tests for the two groups, preparing an a suggested program to teaching Chemistry by Using the a multiple intelligences activities, and achievement test, and a higher thinking skills test in chemistry, a Style of learning and thinking test, The research tools were applied a pre-test on The research sample, it consisted of (58) Students has left learning Hemispheric, divided into two groups, an experimental consisted of (29) Students, and a control consisted of (29) Students, then They studied the unit "material-properties and changes" by using the Suggested program, after that, the two post-tests were applied on the research group, This study was conducted in the second semester of the academic year (1438-1439) AH. The results of the study revealed that there was a statistically significant differences at level (0.05) between the means scores of the First grade secondary Students in the post-test of the achievement and the higher thinking skills test and the Style of learning and thinking test for the post application, The study also revealed that there was an impact of the suggested program on developing achievement and the higher thinking skills and right learning hemispheric and Integrated Style of the first grade secondary Students. In light of these results, the research present some recommendations and suggestions, including training courses for chemistry teachers in service.
Keywords: تدريس الكيمياء -- الذكاءات المتعددة -- التحصيل الدراسي -- مهارات التفكير العليا -- طلبة المرحلة الثانوية